ORGANIZATION OF METHODICAL GAMES USING COMPUTERS IN READING LITERACY CLASSES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The use of computers elevates reading literacy lessons to a new level. This not only facilitates the learning process for students but also teaches them how to work with digital technologies. The article discusses the significant importance of creating an interesting, effective, and creative environment for students through computer technologies in enhancing the quality of the educational process.